Implementasi Edukasi Kesehatan Melalui Media Leaflet untuk Meningkatkan Kestabilan Kadar Glukosa Darah pada Pasien Diabetes Militus di Rumah Sakit Sumber Hidup GPM Ambon - Yulianti Ely; Zulfikar Peluw (Lembaga Pengembangan Kinerja Dosen, 2024)
Hyperglycemia is the main characteristic of diabetes mellitus (DM) disease characterized by an increase in blood sugar levels above the normal threshold (200 mg/dL) which can be caused by relative or absolute insulin deficiency, or by cellular resistance to insulin action. Hyperglycemia is one of the metabolic disorders with a high risk of hospitalization and disability, especially in patients with diabetes mellitus with an increasing prevalence. To provide an overview of the implementation of health education through leafleat media to improve the stability of blood glucose levels in patients with diabetes mellitus at the GPM Ambon Source of Life Hospital. Subject Research Patient was Mrs. R in the Atalia Room of Sumber Hidup Hospital on May 16-17, 2022. The research found that Mrs. R did not understand several things about the stability of blood glucose levels. The nursing diagnosis raised in the patient is the risk of blood glucose instability. Nursing action is to provide health education about the lack of exposure to information about Hyperglycemia, Mrs. R can understand the stability of blood glucose levels. Based on the results of research conducted in the Atalia room at the GPM Ambon Living Source Hospital on May 16-17, 2024 in patient